Scope of Competition Related Trips Flexibilities for Protecting Public Health in Developing Countries (Dhaka University Law Journal, 2025)
The TRIPS agreement has consciously preserved a realm of policy space for its member states. It affords the member states the latitude to tailor the deployment of competition law as a tool of flexibility to place constraints on the exercise of intellectual property rights. Nonetheless, a measure of uncertainty prevails concerning the optimal utilization of this policy leeway, particularly within countries that lack an extensive history of enforcement of competition law and policy, due to the intricate interplay between intellectual property and competition concerns. Now, the operation of competition law must not curtail someone’s patent rights. At the same time, a patent holder must not use his exclusive rights to adversely affect competition in the market. Articles 7 and 8- reliant interpretation of TRIPS allow for a pro-competitive effect of the TRIPS Agreement requiring exploitation of patent rights without infringing domestic competition laws. Articles 8(2), 40, and 31(k) of the TRIPS grant the World Trade Organization (WTO) Members the prerogative to invoke compulsory licensing as a corrective measure against such anti-competitive behaviors. At the same time, TRIPS member states are obligated to not use competition law to undermine patent holders’ exclusive rights. The article aims to provide guidance and recommendations for developing countries on optimizing the balance between competition and patent laws within the TRIPS framework.Dhaka University Law Journal Vol.35, Issue.2, December 2024 P. 223-247